2017
DOI: 10.1089/bfm.2016.0166
|View full text |Cite
|
Sign up to set email alerts
|

After Chemotherapy Treatment for Maternal Cancer During Pregnancy, Is Breastfeeding Possible?

Abstract: Women who undergo chemotherapy during a pregnancy are more likely to report breastfeeding difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Breastfeeding is allowed if there is no ongoing chemotherapy or targeted therapy, if the time since last administration is at least 3 weeks [76].…”
Section: Obstetrical Carementioning
confidence: 99%
“…Breastfeeding is allowed if there is no ongoing chemotherapy or targeted therapy, if the time since last administration is at least 3 weeks [76].…”
Section: Obstetrical Carementioning
confidence: 99%
“…Chemotherapy. Patients who receive chemotherapy during pregnancy demonstrate markedly reduced lactational ability, particularly when they receive therapy earlier during pregnancy and/or when they complete more cycles 30 (Level 3). Chemotherapy is contraindicated during the first trimester and generally is paused 3 to 4 weeks preceding delivery 24 (Level 4).…”
Section: (Level 4)mentioning
confidence: 99%
“…One study compared women who underwent chemotherapy during pregnancy with non-exposed women. That study found a significant difference in patient perception of reduced milk supply and a greater need to supplement the diets of their infants [21].…”
Section: Discussionmentioning
confidence: 99%